Paternal Pre-Pubertal Smoking: Small RNAs, Lasting Marks, and the Hidden Legacy of Early Exposure - Aayush Goyal (Emerging Trends in Personalized Medicines, 2025)
While the negative effects of maternal smoking during pregnancy are well-established, the lasting and transgenerational impact of paternal pre-pubertal smoking remains a critical, underexplored area. Emerging evidence in sperm epigenetics suggests that cigarette exposure during early male development may create persistent molecular imprints that can affect the health of future offspring. ​This phenomenon is rooted in the fact that heredity extends beyond the DNA sequence. Sperm carry a complex epigenetic cargo, including small non-coding RNAs (like microRNAs and piRNAs) and DNA methylation marks, which regulate gene expression without altering the underlying genetic code. The period of adolescence, when spermatogonial stem cells are undergoing rapid proliferation, represents a particularly sensitive developmental window. Exposure to cigarette smoke constituents during this time—including nicotine and reactive oxygen species—can disrupt germ cell maturation and permanently modify the epigenetic 'blueprint'. ​The proposed transgenerational pathway involves three steps: toxicants from cigarette smoke reach the developing testes (Exposure); germ cells respond by altering their DNA methylation and small RNA expression (Epigenetic alteration); and these altered marks modulate gene expression in the zygote upon fertilization, leading to long-term physiological changes (Embryonic influence). Human epidemiological studies support this, showing that children of men who began smoking before puberty have higher risks of obesity, asthma, and accelerated epigenetic aging. ​This body of work challenges the traditional view that only maternal factors shape the next generation. If validated, these mechanisms underscore the urgency of tobacco-control efforts targeting adolescents and highlight the need for sperm epigenetic biomarkers to assess exposure history and counsel prospective fathers.
Keywords: Biological; DNA; RNA; Transgenerational Transmission; obesity; paternal pre-pubertal smoking